Public benefits of private lands conservation: exploring alternative compensation mechanisms - Seidl, Andrew, author; Schwartzentruber, Ryan, author; Hill, Rebecca, author (Colorado State University. Libraries, 2018)
We use a benefit transfer approach to estimate the total value of the ecosystem services on private lands protected by conservation easements to Coloradoans. If we consider an average acre of conserved land in Colorado, annual ecosystem service benefits per acre range from $849 (using minimum values) and $995 (using maximum values) per acre per year and in the range of $2-2.3 billion in total value per year (2018 dollars). In 2012, NRCS established GARCs for the Grassland Reserve Program (GRP) and Wetland Reserve Program (WRP) with rate caps ranging from $170 per acre to $2,240 per acre-year depending on the easement type, the region and the land type conserved. For illustration, the average GARC payment for a parcel in our dataset would have been $1,061 per acre-year conserved (2018 dollars). Estimated annual benefits provided by these easements fall between $4.4 million and $4.6 million. The annualized benefits in perpetuity provide $88-$93 million, using a 5% discount rate. Under the GARC methodology, the payment would have been 4-15 percent more per acre than under the appraisal-based system. Our results show that, regardless of payment methodology, private lands conservation using conservation easements provides positive benefits to the state of Colorado, and that these benefits far exceed the costs. Moving toward a public benefits valuation approach from the current opportunity cost approach has the potential for improved returns to taxpayer dollars due to attracting higher valued properties to the programs.
September 2018.